APPROPRIATE MODELS FOR MEASURING INTANGIBLE ASSETS AND THEIR IMPACT ON THE CASH FLOWS OF THE ECONOMIC UNIT: AN APPLIED STUDY ON A SAMPLE OF IRAQI ISLAMIC BANKS - Zainab Hadi Mahdi (Scholar Express Journal, 2023)
The research aims to address the most important models for measuring intangible assets in a sample of Iraqi Islamic banks, with determining which of these models is more effective in measuring these assets and showing their impact on cash flows in a way that suits the environment of the Islamic banking industry and the accompanying developments and changes, several and successive. The research was applied in a sample of Iraqi Islamic banks, which are the Trust International Islamic Bank, Elaf Islamic Bank and Kurdistan International Islamic Bank for the period (2017-2020). The (Tobin's Q) model was used to measure the tangible assets in these Islamic banks, and the research concluded that the measurement of intangible assets positively affects the cash flows in Islamic banks in a way that suits the changes that accompanied the banking environment
Keywords: intangible assets; cash flows; Iraqi Islamic banks